A Meta-Analysis of Consumer Behavior and Sustainable Marketing: An Evidence-Based Literature Review - Kristiana Sri Utami; Bhenu Artha; Novita Sari; Estri Nurahayu (Multidisciplinary Journal of Education , Economic and Culture, 2026)
This meta-analysis synthesizes the available academic evidence on consumer behavior in the context of sustainable marketing to examine the psychological, social, and economic drivers of green consumption, barriers to sustainable purchasing, and effective marketing strategies. The study uses a meta-analysis method to quantitatively combine data from multiple independent studies into a single, cohesive conclusion. The results indicate that environmental concern, positive attitudes, and perceived values are consistently strong predictors of sustainable purchase intentions. However, a significant attitude-behavior gap exists, wherein positive attitudes toward green products do not always translate into actual purchasing action. This gap is primarily driven by economic barriers like price sensitivity toward premium pricing and complex psychological defense mechanisms. Furthermore, greenwashing significantly triggers consumer skepticism and brand distrust, which negatively impacts green purchase intentions. Conversely, authentic corporate social responsibility (CSR) initiatives, eco-label visibility, and transparent communication foster brand trust and loyalty.